Polymorphisms of Tumor Necrosis Factor Alpha in Moroccan Patients with Gastric Pathology: New Single-Nucleotide Polymorphisms in TNF-α−193 (G/A) - A. Essadik; H. Jouhadi; T. Rhouda; S. Nadifiyine; A. Kettani; F. Maachi (Mediators of Inflammation)
Polymorphisms in tumor necrosis factor alpha (TNF-α) gene are emerging as key determinants of gastric diseases. The TNF-α−308 (G/A) and TNF-α−238 (G/A) single-nucleotide polymorphisms SNPs are the most extensively studied. However, all these studies are conducted in Caucasian and Asian populations. Thus, for the first time in Africa, we sought to investigate whether polymorphisms in TNF-α gene were associated with the development of gastric pathology in Morocco. Two SNPs located in the promoter region (positions −308 and −238) in TNF-α gene were genotyped in 244 individuals (170 patients and 74 healthy controls). Odds ratios (ORs) and 95% confidence intervals (CI) were estimated using logistic regression analysis. The TNF-α−238 (G/A) genotype was significantly associated with a high risk of gastritis and gastric cancer (GC) (P=0.001 and P=0.002, resp.). Furthermore, a new polymorphism located in the promoter region at position −193 in TNF-α gene was identified. The distribution of this SNP was markedly different in patients suffering from ulcers. The association between TNF-α−193 (G/A) genotype and high risk of ulcer was significant (P=0.03). These results suggest that the TNF-α−193 (G/A) allele has a protective function against gastric cancer by developing ulcer.